Contribution to the study of the structural, Electronic and optical properties of CuO and Cu2O materials by CASTEP - Chennafi said; Laboukhi mohamed lamine; ENC/ Bouchama idris (University of M'sila, 2024)
EN This study aims to investigate the structural, electronic, and optical properties of CuO and Cu2O materials with GGA-PBE approximations using the CASTEP code. Computer modeling was employed to study the atomic arrangement and electronic structure of these materials. The optical properties of these materials were also investigated using quantum calculations. The resulting findings provide deep insights into the properties of these materials and highlight the utility of CASTEP in studying physical properties. The obtained results are consistent with the theoretical and experimental values cited in the literature. The characterizations of CuO and Cu2O materials suggest that these materials have a significant potential to be used in photovoltaic devices. FR Ce travail vise à étudier les propriétés structurelles, électroniques et optiques des matériaux CuO et Cu2O avec des approximations GGA-PBE à l'aide du code CASTEP. La modélisation informatique a été utilisée pour étudier la disposition atomique et la structure électronique de ces matériaux. Les propriétés optiques de ces matériaux ont également été étudiées à l’aide de calculs quantiques. Les résultats qui en résultent fournissent des informations approfondies sur les propriétés de ces matériaux et mettent en évidence l'utilité de CASTEP dans l'étude des propriétés physiques. Les résultats obtenus sont cohérents avec les valeurs théoriques et expérimentales citées dans la littérature. Les caractérisations des matériaux CuO et Cu2O suggèrent que ces matériaux ont un potentiel important pour être utilisés dans les dispositifs photovoltaïques.
Keywords: Cu2O; CuO; CASTEP software; structural; electronic and optical properties.